Injectable Controlled Release Drug Delivery Systems - Sheikh, Aijaz A. (Asian Journal of Pharmaceutics (AJP), 2016)
Nowadays conventional dosage forms of drugs are rapidly being replaced by the new and the novel drug delivery systems. Among, these the controlled release/sustained release dosage forms have become extremely popular in modern therapeutics. In the last few years, sustained release injections have developed. At targeted site, these injections showed the prolong effect of drug. Decrease in side effects, lesser frequency of dose, maximum dose-efficacy relationship, and improved patient compliance are the benefits received by controlled release of drugs. To the systemic circulation, parenteral drug delivery can achieve easy access with rapid drug absorption. It is always advantageous to achieve the systemic drug levels within the therapeutically effective concentration range of drug for obtaining the better treatment. With the arrival of novel carriers, the research in parenteral sustained release technologies has received huge boost up. So, many injectable sustained release products have received regulatory approval and launched in the pharmaceutical market. In the present review, efforts were put forth on the rationale and most recent progress done in the development and formulation of parenteral controlled release systems. The review focused on the current long-acting injectable preparations with special attention to marketed products.